A Combinational Strategy Mitigated Old-Aged Petroleum Contaminants: Ineffectiveness of Biostimulation as a Bioremediation Technique - Garousin, Hamidreza; Pourbabaee, Ahmad Ali; Alikhani, Hossein Ali; Yazdanfar, Najmeh (Frontiers in Microbiology, 2021)
Hydrocarbon contamination emerging from the crude oil industrial-related activities has led to severe environmental issues. Prolonged contamination with the constant infiltration of crude oil into the soil is a severe problem in remediating contaminated soils. Hence, the current study focuses on comparing various bioremediation strategies, thereby isolating native bacteria competent to reduce TPH in both liquid and microcosm environments in an old-aged petroleum hydrocarbon contaminated soil. Assays in the modified 6SW-Vit medium after seven days of incubation revealed that Bacillus altitudinis strain HRG-1 was highly hydrophobic and had a suitable ability to decrease surface tension (40.98%) and TPH (73.3%). The results of biodegradation in the microcosm proved that among the designated treatments, including bio-stimulated microcosm (SM), bacterialized microcosm (BM), a combined bio-stimulated microcosm and bacterialized microcosm (SB), and natural attenuation (NA), the SB treatment was the most effective in mitigating TPH (38.2%). However, the SM treatment indicated the lowest TPH biodegradation (18%). Pearson correlation coefficient among microcosm biological indicators under investigation revealed that soil basal respiration had the highest correlation with the amount of residual TPH (r = -0.73915, P < 0.0001), followed by the microbial population (r = -0.65218, P < 0.0001), catalase activity (r = 0.48323, P = 0.0028), polyphenol oxidase activity (r = -0.43842, P = 0.0075), and dehydrogenase activity (r = -0.34990, P = 0.0364), respectively. Nevertheless, considering the capability of strain HRG-1 and the higher efficiency of the combined technique, their use is recommended to diminish the concentration of petroleum hydrocarbons in hot and dry contaminated areas.